SAÚDE DA FAMÍLIA - IMPACTO NO MODO DE ATENÇÃO E NOS INDICADORES DE SAÚDE - KOPF, AGUIDA W.; SAND, ISABEL C. P. V. D.; TUSSET, JOSIANE; FRANZ, LÍGIA B. B.; BUSNELLO, MARISTELA B.; BARTA, RENATA L. (Salão do Conhecimento, 2013)
Resumo